Interpretasi kejurubahasaan jurubahasa - Noraini Ibrahim-Gonzalez, author 563410; Noraiha Noordin, author 563411 (Kuala Lumpur : Dewan Bahasa dan Pustaka, 2013)
Includes bibliographical references and index